Analysis Level Satisfaction Student in Learning Physics - Nadrah, Nadrah (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The population in this study were students of class X- IPA - 2 SMA Negeri 2 Makassar with a size of population of 68 students. Because all population units can be reached and it is possible not If data is damaged, this study uses census research. As for the variables that studied in this study, namely: (1) satisifier in studying physics which includes achievement individual achievement of students in physics lessons, recognition or self-actualization in PBM physics, learning physics itself, self-responsibility to study physics, and development individual potential of students in studying physics, and (2) dissatisfiers in studying physics which includes family socio-economic conditions, PBM physics conditions, policies and administration school (teachers), student relations, and the quality of teacher supervision. Data collection tools that used in this research is a questionnaire. The data collected were analyzed by the technique of descriptive. The results showed that student satisfaction in studying physics can achieved by satisfiers factors. Student dissatisfaction in studying physics will occur by condition dissatisfier. Based on results study on could it is concluded that if condition satisfiers could achieved, so will give motivation for learn physics, so that possible capable create satisfaction student in learn physics, which Finally, good achievement will be obtained in studying physics. If the condition dissatisfiers could achieved, so no will give motivation for learn physics, so that it is possible to create student dissatisfaction in studying physics that finally won't obtained achievement achievement good in learn physics.